2017
DOI: 10.1371/journal.pone.0176233
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes of severe dengue patients presenting with sepsis in a tropical country

Abstract: BackgroundDengue is a common cause of infection in adults in tropical countries. Sepsis is a syndrome of systemic manifestations induced by infection of any organisms; including bacterial, fungal and viral agents. Here, we investigated the diagnosis, management and outcomes of dengue patients presenting with sepsis in a prospective study of community-acquired sepsis in Thailand.MethodsFrom June to December 2015, 874 adult patients (age≥18 years) with suspected or documented community-acquired infection, with ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…One study in Thailand found that ~14% of patients diagnosed with sepsis (Sepsis-2 definition) tested positive for dengue viruses upon re-analysis of banked serum samples by PCR ( 71 ). Of the patients who were diagnosed with dengue by PCR from banked serum samples five had died, of which four had been diagnosed with sepsis but not dengue infection.…”
Section: Aetiology Of Viral Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…One study in Thailand found that ~14% of patients diagnosed with sepsis (Sepsis-2 definition) tested positive for dengue viruses upon re-analysis of banked serum samples by PCR ( 71 ). Of the patients who were diagnosed with dengue by PCR from banked serum samples five had died, of which four had been diagnosed with sepsis but not dengue infection.…”
Section: Aetiology Of Viral Sepsismentioning
confidence: 99%
“…Of the patients who were diagnosed with dengue by PCR from banked serum samples five had died, of which four had been diagnosed with sepsis but not dengue infection. It was suggested that it may prove beneficial to increase testing for dengue viruses in patients presenting with sepsis to ensure the patient receives appropriate treatment ( 71 ).…”
Section: Aetiology Of Viral Sepsismentioning
confidence: 99%
“…We conducted a secondary analysis of 9 data sets: 8 cohort studies (5 prospective and 3 retrospective) and 1 randomized clinical trial. [8][9][10][11][12][13][14][15] Of the countries represented in this study (Bangladesh, Haiti, India, Indonesia, Myanmar, Rwanda, Sierra Leone, Sri Lanka, Thailand, and Vietnam), 3 are classified as low income, 6 as lower middle income, and 1 as upper middle income by the World Bank. 16 Patients were recruited to the cohorts from a range of hospital settings, including small community hospitals, military hospitals, rural regional hospitals, national referral hospitals, and specialty infectious disease hospitals.…”
Section: Study Design Setting and Populationmentioning
confidence: 99%
“…In addition, recent report from Thailand indicated that a number of adult patients who died of dengue virus are misdiagnosed as severe sepsis and septic shock. 13 Thus diagnosis of dengue based on clinical features alone is difficult. Rapid NS1 antigen detection, using ICT method, is the most widely used method for the diagnosis of dengue in endemic areas.…”
Section: Discussionmentioning
confidence: 99%